First record of the blue-and-yellow grouper Epinephelus flavocaeruleus (Lacepède 1802) (Perciformes: Epinephelidae) from the Borneo waters, Malaysia - Loh, Kar-Hoe; Poong, Sze-Wan; Du, Jianguo; Ong, Joyce Jia Lin; Zheng, Xinqing; Li, Yuan; Hu, Wenjia (Zootaxa, 2024)
Groupers of the family Epinephelidae constitute a diverse and commercially valuable group of reef fishes globally. They comprise an assemblage of carnivorous marine fishes, comprising more than 177 species across 16 genera. The epinephelid genus Epinephelus, which consists of over 90 species, is found worldwide in the tropics and subtropics. To date, the ichthyofauna of Malaysia has documented a total of 43 epinephelid species. Apart from these, Epinephelus flavocaeruleus (Lacepède, 1802), commonly known as the blue-and-yellow grouper, is rarely reported in the Indo-Pacific Ocean. The present study extends the documented distribution range of E. flavocaeruleus eastwards from the Andaman Sea to the Borneo waters of Sabah, Malaysia. Five specimens of the blue-and-yellow grouper were collected from a local fish market. Species identification was confirmed by the color patterns and DNA barcoding of 630 base pairs of the cytochrome C oxidase I gene for all E. flavocaeruleus specimens, Epinephelus cyanopodus (Richardson, 1846), and 10 closely related Epinephelus species. The interspecies genetic distance ranged from 0.002–0.168. Results from the Templeton, Crandall, and Sing (TCS) haplotype network analysis and maximum likelihood phylogeny based on the COI marker indicate a close genetic relationship between E. flavocaeruleus and E. cyanopodus. However, we refrain from proposing any taxonomic revisions given that more in-depth studies using multiple molecular markers or phylogenomic analysis on a larger sample size are necessary to confirm the taxonomic status of both species. This study significantly contributes to a better understanding of the taxonomy, phylogenetic relationship, and genetic diversity of E. flavocaeruleus.